Ascorbic acid in egg injection minimizes the effects of fasting between hatching and housing of broiler chicks - Iglesias, Dayane Lilian Pires [UNESP] (2015)
The duration of pre-housing fasting may determine the chick’s weight loss, impairing their performance during the rearing. Management’s practices to minimize the effect of this fast are extremely important to the success of broilers rearing. The aim of this study was to check if the ascorbic acid injection (AA) in egg avoids or minimizes the effects of pre-housing fasting in broilers chicks. Fertile Cobb® broiler eggs from hens at 29 weeks of age were used. The experimental design was completely randomized in a factorial arrangement 2 x 4 x 2, and two sex (males and females), with 4 treatments (non-injected eggs and chicks submitted to fasting; not injected eggs and chicks fed with water and feed ad libitum; eggs injected with 1 μg de AA/150 μL of water and chicks submitted to fasting; eggs injected with 3 μg de AA/150 μL of water and chicks submitted to fasting) with 2 different ages (48 and 72 h after hatching). Eggs injected with 1 mg of AA preincubation has increased the hatching by 14.2% avoiding the negative effect of fasting on the weights of the chicks till 48 h after hatching, however, feed intake after this period of fasting is critical, independent of the AA injection, the association of AA injection and feed intake, are important managements to avoid weight loss of pre-housing chicks.